2018
DOI: 10.2106/jbjs.18.00283
|View full text |Cite
|
Sign up to set email alerts
|

Update on Misrepresentation of Research Publications Among Orthopaedic Surgery Residency Applicants

Abstract: Background: Our 2 previous studies (1999, 2007) examining misrepresentation of research publications among orthopaedic residency applicants revealed rates of misrepresentation of 18.0% and 20.6%, respectively. As the residency selection process has become more competitive, the number of applicants who list publications has increased. The purpose of this study was to determine current rates of research misrepresentation by orthopaedic surgery applicants. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(40 citation statements)
references
References 20 publications
4
36
0
Order By: Relevance
“…A follow-up study reported only 13 of 1100 (1.18%) papers as inaccurate during the 2016-2017 application cycle, which is much closer to the rate of inaccuracy found in our study. 10 The slight increase in our inaccuracy rate could be because the SF Match does not require a PMID field for each citation. Fellowship applicants may also demonstrate more diligence when reporting their research experience.…”
Section: Discussionmentioning
confidence: 97%
“…A follow-up study reported only 13 of 1100 (1.18%) papers as inaccurate during the 2016-2017 application cycle, which is much closer to the rate of inaccuracy found in our study. 10 The slight increase in our inaccuracy rate could be because the SF Match does not require a PMID field for each citation. Fellowship applicants may also demonstrate more diligence when reporting their research experience.…”
Section: Discussionmentioning
confidence: 97%
“…An increasingly qualified applicant pool poses a difficult challenge for faculty involved in screening/selecting applicants [7]. As a result, scholarly activity is now routinely used as an important stratification metric since this is a proxy of an applicant's diligence at task completion, work ethic, and academic potential during residency [6,7].…”
Section: Discussionmentioning
confidence: 99%
“…Published articles/abstracts were categorized by type. Misrepresentation was defined in accordance with criteria established by Meeks et al with minor modifications as follows: (1) non-authorship of a published article in which authorship was claimed, (2) claimed authorship of non-existent/unverifiable article, (3) self-promotion to a higher authorship status within a published article, and (4) non-peer reviewed article/abstract reported as peer-reviewed [7]. The number of podium and poster presentations were recorded for applicants but were not included in misrepresentation analyses.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… 3 4 5 6 7 8 9 10 11 12 13 14 15 16 Rates of misrepresentation in orthopaedics have significantly decreased over the last 20 years, likely due to the advent of including PubMed identification numbers in the Electronic Residency Application Service (ERAS) standardized residency application. 6 , 10 , 12 While previous studies have examined publication misrepresentation among verified publications, no study to date has examined the outcomes of publications listed as “submitted” at the time of application to orthopaedic surgery residency. These “Submitted” publications have no associated PubMed identification, which prevents their outcomes from being verified during the residency application process.…”
mentioning
confidence: 99%